"Thinking and Working Politically": The case of donor‐supported reform coalitions in the Philippines. (2nd December 2020) - Clarke, Gerard
Abstract: Motivation: Reform coalitions represent a potential means for donors to support macro‐political reform in developing countries, enabling them to avoid the limitations of micro‐political or public sector reform where appropriate circumstances exist. Donor support for reform coalitions, however, is difficult to engineer and fraught with political risk, including the risk of partisan taint. Purpose: This article therefore explores the efforts of Australian Aid and the World Bank to promote reform coalitions and constituencies in the Philippines during the presidency of Benigno S. Aquino III (2010–2016) and to institutionalize the reform agenda of his administration. Approach and Methods: It draws on a range of sources including programme design documents, mid‐term and end‐of‐term reviews, and contextual policy documents. It also draws on economic and governance data sets to explore relevant correlations. Findings: It finds that second‐generation reform coalitions brought together stakeholders from government, the private sector and civil society and promoted economic and other reforms. These donor strategies arguably failed, however, with the election of Rodrigo Duterte in May 2016. He was critical of Aquino's record in office and ostensibly committed to reverse engineering many of the Aquino administration's achievements. The article critiques a governance‐centric explanatory chain of causation and proposes an expanded politics‐centric chain. Policy Implications: In conceptual terms, planning of reform coalition activities must better account for dominant coalitions and the political settlements which they underpin, and must set out explicit theories of change, specifying distinct political pathways to change. In operational terms, donors must work to avoid traditional "transactional" relationships in favour of more innovative "transformative" ones and must balance "strategic opportunism" with strategic retreat and adaptation where necessary.